Procedures and strategies in the English translation of cultural words in Mowlana Jalaludin Rumi's Mathnavi - Kermani, Mozhgan Mohajerin (2013)
Western culture has long had a hegemonic influence on translation, resulting in the choice of strategies and procedures that favour the Western readers, for instance, domestication strategies that bring the text closer to the target reader instead of maintaining the original cultural elements. This position also influenced Persian-English translation. This research is on the use of domestication and foreignization strategies in the translation of cultural elements from Persian into English in Jalaluddin Rumi’s Mathnavi. Its purpose is to describe and compare the application of domestication and foreignization strategies utilized by five renowned translators in order to find out the dominant overall strategy used as well as the dominant procedures employed in translating specific categories of cultural words. The research also discusses the socio-cultural factors contributing to the choice of strategies and procedures used by translators. The analysis was based on Venuti’s (1995) dichotomy of domestication and foreignization. Cultural words were identified and classified on the basis of Newmark’s (1988) categorization of cultural words. Newmark’s model had to be expanded and refined to include all cultural words found in the Mathnavi before the analysis could be carried out. In line with the objectives of the study, Toury’s (1995) methodology of descriptive translation studies (DTS) was selected, thus locating the source and target texts in their socio-cultural and historical contexts. Translators’ individual backgrounds were considered as another factor influencing translators’ selection of strategies. The findings show that the procedures employed most frequently were literal translation, cultural adjustment, and explanation; while the most dominant overall strategy used is domestication. The findings also indicated a variation in individual translators’ use of the main strategies. The choice of the strategies seemed to be influenced by factors related to socio-cultural and historical contexts, such as Western cultural hegemony, and individual factors such as translators’ prior familiarity with Persian culture and their interest in the culture, as well as their academic backgrounds and fields of study. The findings of this research contribute to a more in-depth understanding of the process involved in the translation of cultural words in Rumi’s Mathnavi within the context of Western cultural hegemony, which has hitherto been lacking. Information on translators’ choice of translation procedures for translating each category of cultural words also provides a useful guideline for translators of similar literary pieces from Persian to English.